Trabalho com o gênero conto fantástico: uma análise das capacidades de linguagem - LIMA, Maria Maiane Filomeno (2025)
The present study introduces the fantastic short story genre and an analysis of language capacities. We address the study of teaching textual genres in Portuguese language classes. To this end, we highlight how the didactic sequence, as a teaching tool, contributes to students performance. The didactic sequence challenges traditional approaches, offering endless possibilities for working with genres in the classroom. In a way, it is a teaching strategy that aids in learning development. Thus, we aim to present the work with the short story genre and the use of language capacities in the written productions of a 7 grade class in elementary school, demonstrating how working with this genre correlates with writing. The research was conducted at Escola Municipal 13 de Maio, in the city of São Luís Gonzaga do Maranhão/MA. The central question guiding this research is: how does the development of students language capacities manifest in their textual productions? Accordingly, our general objective is to investigate the development of 7 grade students language capacities in the production of fantastic short stories. Regarding the specific objectives, we seek to evaluate textual productions using a checklist; analyze students written productions concerning the grammatical and structural elements that compose the fantastic short story genre; and utilize the didactic sequence as a tool in the textual production process. Concerning the methodological procedures employed, we adopted a qualitative research approach, specifically action research. In this methodology, both the research and the researcher are actively engaged in the study as participant-authors. As for the theoretical framework, we rely on the theoretical assumptions of Bronckart (2006), Koch (2015), Gotlib (2006), Marcuschi (2008), Marcuschi (2003), and Schneuwly et al. (2019). Thus, we emphasize the importance of the didactic sequence and the study of genres for students' social and cognitive development, as well as for enhancing the teaching and learning process in portuguese language classes.